Zur Frage des Eisabbaues in der Randzone des Alpenkörpers - Gareis, Josef (ERDKUNDE, 1979)
This contribution is the first part of a comprehensive study being made in order to explain how the glaciers flowing from the Alpine gates at the time of the main Würm era were reduced at the turn of the Holocene. As has been shown in the study the dead ice fields of the Bavarian Alpine Foreland as witnesses of the manner of disappearance of ice in the late Würm period it did not happen by a ice regression, as has generally been supposed so far, but by a melting away of the tongues from above to below, as soon as replacements from the central Alpine ice-stream network were no longer able to traverse the high transfluence passes. Sub-glacial thresholds at the bottom of the tongue basin moreover aggravated the further transportation of the ice. The resulting thinning-out of the glacier tongue led to stagnation and disintegration of the ice. Extensive dead-ice remnants, however, remained behind and were surrounded with rubble by melted snow. Erosion fillings and marginal terraces generated in this way permit determination of the progress of the melting process within a given time. Against the background of a future investigation of the reduction of ice in the foreland (co-ordination of investigations by B. Frenzel, Stuttgart-Hohenheim) and in the Alps (Alpine Glacier and Ice Age Research at the Geographical Institute of Innsbruck University) an attempt is being made to apply these causes of ice disintegration to a selected section of the northern edge of the Alps. The Inzell Basin (Upper Bavaria) offers a particularly suitable field of evidence for this, since the glacier tongue of the Würm period never reached the Foreland. First findings from the Aschau Basin in the Chiemgau meanwhile produced a similar picture of ice reduction at the head of the Pleistocene Prien Glacier. In the Kossen Basin (Tyrol) on the other hand comparable traces of ice disintegration are missing. It is likely that at this central place of distribution in the midst of the former ice-stream network there was a different mode of ice reduction together with gradually decreasing supplies. The detailed mapping of the area under investigation is presented by a GNK legend, which is adjusted to the specialties of the glacial or fluvio-glacial character of the region.